Does culture trump money? Employment and childcare use of migrant and non-migrant mothers of pre-school children in Germany - Christina Boll; Andreas Lagemann (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2018)
This study investigates the employment and childcare use behaviour of migrant and non-migrant mothers in Germany. We use the waves 2007-2015 of the German Socio-Economic Panel study (SOEP), including the migrant samples M1 and M2, to identify significant associations between migration background and employment probability, working hours, and childcare usage probability under control of human capital, household, milieu, and macro factors. We correct for self-selection in employment and potential endogeneity of childcare use. We do not find an additional contribution of a migrant background to mothers' use of childcare. However, among self-immigrated mothers with a youngest child aged 3 to 5, roots in Southeastern Europe are associated with lower childcare use. Further, a direct (indirect) migrant background, compared with no migrant background, is associated with a 6.3 % (5.9 %) lower probability of employment for mothers of youngest children under 3 years of age with otherwise identical maternal characteristics. For mothers of youngest children aged 3-5, the figure is 8.0 % (6.7 %). Mothers of youngest children under 3 years (aged 3-5 years) with roots in Arab and other Muslim countries have a 7.1 % (21.1 %) lower probability of employment. In addition, the likelihood of gained employment increases with the length of stay in Germany. There are no significant associations of the migration background with the (conditional) weekly working hours of mothers. In summary, it can be seen that, in addition to economic motives, cultural factors and basic orientations and values also shape mothers' everyday practices, as expressed in their employment behaviour and the use of state-subsidized childcare for their children.
Keywords: J220; J130; J610; 330; maternal employment; hours of work; childcare; migration background; milieu; IV techniques; 2SLS; bivariate probit